Influence of ‘atlantic’ potato plant density under different micropropagation methods - Morais, Leticia Manuela de; Ayub, Ricardo Antonio; Grimaldi, Fernanda; Reis, Camila Audrey dos (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2021)
Potato (Solanum tuberosum L.) is among the most produced crops in Brazil. Since its propagation is vegetative, the plant presents problems due to its susceptibility to diseases. Thus, an in vitro propagation has been used to enable the production of quality plantlets with excellent sanitary conditioning in a short period of time. Aiming at optimizing micropropagation, were developed bioreactors that allow the use of a liquid medium, not requiring the use of gelling agents. The objective of this work was to study the effect of explant density for mass production of potato plantlets, using a temporary immersion system (TIS) in comparison to conventional micropropagation. For potato culture, the conventional method, using semi-solid medium, presented better results for most of the variables analyzed when compared to TIS. The treatment using 60 plants was superior to 90 plants for explants fresh mass and the variables ​​callus diameter and number of leaves in TIS, did not presented significant results at the 5% probability level by the F test. Index terms: Biorreactor; in vitro; Solanum tuberosum L.; TIS.